Validating Impedance/pH Sensors for Measuring Oesophageal Transit: A Study Based on Dysphagia and Barium Swallow - Ismail Miah; Terry Wong; Sebastian Zeki; Jafar Jafari (Sensors)
(1) Background: This study validates multichannel impedance/pH (MII/pH) sensors to measure oesophageal impedance transit (EZT). (2) Methods: EZT involved patients rapidly drinking 200 mL of saline during their MII/pH test. During the EZT study, the oesophageal pH sensor was used to exclude gastric acid reflux occurring and interfering with the oesophageal transit. EZTs were compared between (i) asymptomatic and symptomatic patients with dysphagia and (ii) barium swallow study outcomes for normal oesophageal transit and retention. Statistical t-tests, chi-squared tests, receiver operating characteristic curves with Youden’s J Index and regression analysis were conducted. (3) Results: A total of 458 patients (265 females) undertook the transit test during their MII/pH test. Prolonged EZT was found in patients with symptomatic dysphagia (t-statistics 4.28–4.43, p < 0.001) with the cut-off threshold at 1 min in the distal oesophagus for dysphagia symptoms (sensitivity 0.81, specificity 0.75). EZT was significantly higher in patients with retention on the BS test (t-statistics 7.29–8.91, p < 0.001), with the distal oesophageal cut-off threshold at 3.7 min being predictive for retention (sensitivity 0.79, specificity 0.93). Increased EZT in the distal oesophagus showed a direct positive correlation to higher dysphagia severity (r = 0.67, p < 0.001). (4) Conclusions: MII/pH sensors provide a platform to measure oesophageal transit, which was able to explain dysphagia from poor oesophageal clearance and predict the BS test outcome.